Wpływ medium cyfrowego na konstruowanie nowych zależności pisma i obrazu - Smaga, Agnieszka (Załącznik Kulturoznawczy, 2023)
The difference between word and image, known from analog culture, ‘breaks’ at the level of generating digital transmission − Internet media, web applications, websites, web browser. The suggested identity of the ‘material’ aspect of writing and image, defined as the assignment of figures for both, finds its consequences at operational level, that is in means of communication